Effects of N-terminus modifications on the conformation and permeation activities of the synthetic peptide L1A - Moro Zanin, Luciana Puia [UNESP] (2016)
We investigate the effect of the N-terminus modification of the L1A, a synthetic octadecapeptide, on its helical content, affinity and lytic action in model membranes and on its hemolytic and antibacterial activities. L1A and its acetylated analog displayed a selective antibacterial activity to Gram-negative bacteria without being hemolytic. The covalently linked 2-aminobezoic acid to the N-terminus impaired the antibacterial efficacy and increased hemolysis. Despite their lower net charge (+2), N-terminus modifications resulted in enhanced affinity and improved lytic efficiency in anionic vesicles. The analogs also showed higher helical content and consequently higher amphipathicity in these vesicles. The conformational analysis by molecular dynamics simulations in 30 % of TFE/water showed that the hydrophobic faces of the peptides are in close contact with CF3 groups of TFE while the hydrophilic faces with water molecules. Due to the loss of the amino charge, the N-termini of the analogs are buried in TFE molecules. The analysis of the pair distribution functions, obtained for the center of mass of the charged groups, has evidenced that the state of the N-terminus has influenced the possibility of different ion-pairing. The higher complexity of the bacterial cells compared with anionic vesicles hampers to establish correlations structure-function for the analogs.